2008
DOI: 10.1063/1.2960593
|View full text |Cite
|
Sign up to set email alerts
|

On the interatomic electronic processes following Auger decay in neon dimer

Abstract: The accessible relaxation channels of the electronic states of Ne(++)-Ne and Ne(3+)-Ne populated by KLL Auger decay are studied. In particular, we address the "direct" and "exchange" interatomic Coulombic decays (ICDs) and the electron-transfer-mediated decay following the population of one-site states Ne(++)(2s(-2))-Ne and Ne(++)(2s(-1)2p(-1) (1)P)-Ne. Radiative charge transfer of the low lying Ne(++)(2p(-2))-Ne states, three-electron ICD process from the Ne(++)(2s(-2))-Ne states, as well as charge transfer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…(14) and (16). The line strength S (A) i (E A L A ; E A L A ) and transition energies ω i correspond to the deexcitation of the initial state in the case of ETI or pRICD or to the transition between the outer-and inner-valence shells in the case of sRICD.…”
Section: Excited Neutral Atom Amentioning
confidence: 99%
See 1 more Smart Citation
“…(14) and (16). The line strength S (A) i (E A L A ; E A L A ) and transition energies ω i correspond to the deexcitation of the initial state in the case of ETI or pRICD or to the transition between the outer-and inner-valence shells in the case of sRICD.…”
Section: Excited Neutral Atom Amentioning
confidence: 99%
“…Originally ICD was predicted [1] and investigated both theoretically and experimentally [2][3][4][5][6][7] in singly ionized clusters, where one of the constituent monomers had a hole in an inner-valence shell. Later investigations showed that it exists also in excited neutral clusters [8][9][10][11] and in excited doubly ionized clusters that are produced via an Auger decay on one of the monomers [12][13][14][15][16][17]. Thus, there seems to be no restrictions on the nature of the initially excited state and interatomic decay takes place as long as the corresponding channel is energetically accessible.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, Ne 2 has been already subject to many experimental and theoretical studies of ICD (4,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) and thus can be regarded as a well known model system for the ICD process. Secondly, it allows us-due to our experimental technique-to directly compare the change in electron emission between an isolated gas phase atom with one that is embedded in an environment: The dimer consists of a neon atom that is surrounded by a single second atom bound only by the van der Waals force (3 meV or 0.07 kcal∕mol).…”
mentioning
confidence: 99%
“…A similar collective ICD transition of two inner-valence vacancies localized on a single atom is possible in Ne 2 following single-site double Ne 2s ionization [100] and in NeAr dimers after double Ar 3s ionization [101]. The three-electron decay…”
Section: Collective Interatomic Coulombic Decay In Clustersmentioning
confidence: 95%